2018
DOI: 10.1007/s13205-018-1496-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid enhancement of α-tocopherol content in Nicotiana benthamiana by transient expression of Arabidopsis thaliana Tocopherol cyclase and Homogentisate phytyl transferase genes

Abstract: Agrobacterium-mediated transient gene expression have become a method of choice over stable plant genetic transformation. Tocopherols are a family of vitamin E compounds, which are categorized along with tocotrienols occurring naturally in vegetable oils, nuts and leafy green vegetables. This is the first report involving AtTC and AtHPT transient expression in Nicotiana benthamiana and this system can be used efficiently for large scale production of vitamin E. Agroinfiltration studies were carried out in N.be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…The precursors for this metabolites could be increased by the chlorophyll degradation observed in the present study. Another high value product naturally produced during this degradation process was α-tocopherol (Sathish et al 2018 ). Further potential candidate molecules could be lipids and hydrocarbons for biofuels and industrial use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precursors for this metabolites could be increased by the chlorophyll degradation observed in the present study. Another high value product naturally produced during this degradation process was α-tocopherol (Sathish et al 2018 ). Further potential candidate molecules could be lipids and hydrocarbons for biofuels and industrial use.…”
Section: Discussionmentioning
confidence: 99%
“…This Nicotiana species is amenable to agroinfiltration and high level transient gene expression. In addition to pharmaceutical proteins, N. benthamiana has also been exploited as a cell factory for high value or speciality chemicals (Sathish et al 2018 ). Fundamentally, it is also an invaluable resource for determining subcellular localisation and protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Conferring the genetic trait to improve vital nutrient accumulation in the edible parts of staple food crops, such as rice, through metabolic engineering is considered a fast, sustainable and cost‐effective alternative to conventional breeding (Maestre et al, 2017). In earlier reports from our laboratory, enhanced α‐tocopherol levels in the stable transformants of Nicotiana tabacum (Harish et al, 2013a, 2013b) and in Nicotiana benthamiana adopting a transient expression system using A. thaliana tocopherol cyclase (TC) and homogentisate phytyl transferase (HPT) (Sathish et al, 2018) were shown. In the present study, Agrobacterium ‐mediated transformation of Indica rice ASD16 with two genes involved in tocopherol biosynthesis, viz ., TC and HPT, was carried out and the transgenic plants were analysed for the vitamin E (α‐tocopherol) content.…”
Section: Figurementioning
confidence: 95%
“…In the past few years, attempts to genetically overexpressing the tocopherol biosynthetic genes in model plants in order to increase the accumulation of tocopherol and their diverse function have been reported [11,12]. Genetic manipulation of genes encoding individual enzymes in this pathway such as γ-tocopherol methyltransferase (γ-TMT) [13,14], TC [15,16], and Homogentisate phytyl transferase (HPT) [17,18,15]. Kanwischer and co-workers demonstrated that the overexpression of TC/VTE1 enhance the tocopherols level by 7-folds [19].…”
Section: Introductionmentioning
confidence: 99%